Social Interaction of Students with Gadget: Patterns and Experiences during School Time - Auliarachman Diadi, Airlangga; Nurdin, Muhamad Fadhil; Gunawan, Wahyu (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
Technological advancements have rapidly impacted society, transforming the way gadgets are utilized for social interaction. Among students, the use of gadgets for socializing has been on the rise. However, differences in interaction patterns between gadget-mediated and face-to-face interactions have yet to be fully understood. Therefore, this study aims to investigate student social interaction activities through gadgets and in real-life settings. Additionally, the research explores social interaction patterns and experiences among students at SMA IT Plus Bina Bangsa Sejahtera Bogor, a high school that initially prohibited smartphone use during learning but later modified their policy prior to the Covid-19 pandemic. A descriptive qualitative approach was employed, utilizing observation, documentation, and interviews with 30 randomly selected respondents. The study was conducted over a two-month period, from January to February 2023, at SMA IT Plus Bina Bangsa Sejahtera Bogor. The analysis reveals that gadget-mediated interaction patterns involve cooperation, accommodation, assimilation, acculturation, competition, and opposition. Prolonged gadget usage for extended hours was observed, emphasizing their significance in students' lives. Interpretation of gadget-mediated text messages sometimes leads to misunderstandings. However, communication differences between virtual and face-to-face interactions were minimal, as both modes effectively addressed problems. This research deepens our understanding of student social interaction dynamics and highlights the impact of gadget usage on interpersonal communication. It provides insights for schools, families, and policymakers to enhance positive gadget usage and improve the quality of student interactions.